Enhancing Reading Skills Among the Primary Students for the Mokhlan History Content - Thussaneeya Boripis; Wang Hao; Shubham Pathak (Emerging Science Journal, 2025)
Students in Thailand are susceptible to being swayed away from reading. This has been a major challenge for teachers in primary schools, as reading skills are necessary for the development of students. With an innovative approach inclusive of Sustainable Development Goals (SDGs), Creative Base Learning (CBL), and Problem-Based Learning (PBL) along with the theoretical underpinning of Constructivist Theory, this research explores enhancing reading skills among primary school students in Thailand. This research adopts a mixed-method approach with data collection from survey questionnaires, key informant interviews, and focus group discussions. The data analysis involves a t-test and the six hats tool for the qualitative support of the quantitative findings. The findings suggest a lack of interactive creative media tools to inculcate student reading skills. The data depicts a need to repeat the reading test at the primary level and include all the stakeholders, including teachers, students, and parents. The novel contributions of this research include the model emphasizing the role of learning and training among various stakeholders to enhance the reading skills of Mokhlan history. This study paves the way for future research on analyzing the factors responsible for students' lack of 21st-century skills, especially at the primary school level.